Il KOUROS di Reggio: due ipotesi ricostruttive - Bonomi, Simonetta; Paoletti, Maurizio; Pesce, Rosanna (Archeomatica, 2015)
The Kouros from Reggio Calabria is a marble statue whose denomination comes from the Greek word indicating a young man. Therefore, Kouros means "boy”, "child”. In archaeological field, this word is used to indicate the representations of naked male figures, staying in front position with the arms stretched next to the sides and a leg moving forward. The Kouroi give a crystallized image of the male body in the prime of life; they embody the idea of human perfection typical of the greek aristocracy, concerning also ethic and intellectual excellence along with physical thew.